PERSEPSI PENATA RIAS TERHADAP PENGGUNAAN TEKNIK AIRBRUSH DALAM TATA RIAS WAJAH PENGANTIN: PERCEPTION OF MAKEUP STYLE ON THE USE OF THE AIRBRUSH TECHNIQUE in BRIDAL MAKEUP - korn, johanna febriza (Jurnal Tata Rias, 2021)
This study aims to determine the perception of makeup artists on the use of airbrush techniques in bridal makeup. This study uses a qualitative method. Collecting data through questionnaires at the beginning of the study and interviews at the end of the study. The data were analyzed through the stages of data presentation, data reduction and data verification and then tested for credibility using source triangulation. The questions asked to 5 informants who work as bridal makeup artists who use airbrush techniques include educational background, knowledge of airbrush techniques, knowledge of bridal makeup and the impact of using airbrush techniques in bridal makeup. The results showed that: (1) The use of the airbrush technique can produce makeup on the bride's face that is more durable, smooth makeup texture, and the dimensions of the color gradations are blended. (2) The airbrush technique can be applied to several types of cosmetics in the make-up process, including foundation, contour, and blush. In addition, it is also used for coating the results of makeup using conventional techniques. (3) The use of the airbrush technique in bridal makeup can improve the ability, performance, and value of the existence of makeup artists because they have abilities that other bridal makeup artists in general do not have. (4) Airbrush technique is one of the techniques in applying makeup, it looks easy but when used it is difficult. So to be able to use the airbrush technique in bridal makeup, you must have its own expertise in order to produce maximum makeup. (5) There are obstacles in using the airbrush tool, namely the airbrush pen hole is often clogged with dried cosmetic residue. Therefore, makeup artists who use airbrushes are required to take care of every component of the airbrush tool to keep it functioning properly.